Neuroprotection induced by dexpramipexole delays disease progression in a mouse model of progressive multiple sclerosis. (18th April 2020) - Buonvicino, Daniela; Ranieri, Giuseppe; Pratesi, Sara; Gerace, Elisabetta; Muzzi, Mirko; Guasti, Daniele; Tofani, Lorenzo; Chiarugi, Alberto
Abstract : Background and Purpose: Drugs able to counteract progressive multiple sclerosis (MS) represent a largely unmet therapeutic need. Even though the pathogenesis of disease evolution is still obscure, accumulating evidence indicates that mitochondrial dysfunction plays a causative role in neurodegeneration and axonopathy in progressive MS patients. Here, we investigated the effects of dexpramipexole, a compound with a good safety profile in humans and able to sustain mitochondria functioning and energy production, in a mouse model of progressive MS. Experimental Approach: Female non‐obese diabetic mice were immunized with MOG35–55 . Functional, immune and neuropathological parameters were analysed during disease evolution in animals treated or not with dexpramipexole. The compound's effects on bioenergetics and neuroprotection were also evaluated in vitro. Key Results: We found that oral treatment with dexpramipexole at a dose consistent with that well tolerated in humans delayed disability progression, extended survival, counteracted reduction of spinal cord mitochondrial DNA content and reduced spinal cord axonal loss of mice. Accordingly, the drug sustained in vitro bioenergetics of mouse optic nerve and dorsal root ganglia and counteracted neurodegeneration of organotypic mouse cortical cultures exposed to the adenosine triphosphate‐depleting agents oligomycin or veratridine. Dexpramipexole, however, was unable to affect the adaptive and innate immune responses both in vivo and in vitro. Conclusion and Implication: The present findings corroborate the hypothesis that neuroprotective agents may be of relevance to counteract MS progression and disclose the translational potential of dexpramipexole to treatment of progressive MS patients as a stand‐alone or adjunctive therapy.